2006
DOI: 10.1109/tns.2006.885109
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Modifications of the Electrical Characteristics of Nanocrystal Memory Cells and Arrays

Abstract: Proton irradiation on Nanocrystals Memories\ud produces peculiar radiation effects on the electrical\ud characteristics of these devices, owing to their thin tunnel oxide\ud and to the presence of nanocrystals replacing the Flash memory\ud conventional floating gate. In this work we show that the data\ud retention capability is compromised only after high fluences and\ud that irradiated devices do not show accelerated degradation\ud during subsequent electrical stresses. The presence of\ud nanocrystals instead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The first work on prototype NCM intended to evaluate different cell designs and processes [19] presented results on nanocrystal memories, favorably comparing with those on currently available commercial flash technology, and indicating a promising future for NCM even for space and military applications. In [20] and [21] we showed promising results regarding NCM in terms of both single event and total irradiated dose effects, highlighting that NCM's can tolerate radiation doses as high as several Mrad's.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The first work on prototype NCM intended to evaluate different cell designs and processes [19] presented results on nanocrystal memories, favorably comparing with those on currently available commercial flash technology, and indicating a promising future for NCM even for space and military applications. In [20] and [21] we showed promising results regarding NCM in terms of both single event and total irradiated dose effects, highlighting that NCM's can tolerate radiation doses as high as several Mrad's.…”
Section: Introductionmentioning
confidence: 86%
“…In the last years it has been demonstrated that NCMs have a very good potential in retaining the electric charge within the nanocrystal layer after irradiation [19]- [21]. However, most of these results have been obtained by studying the "average" characteristics of CAST (Cell Array Stress Test) structures, featuring 256 kbit cells with parallel connection.…”
Section: Introductionmentioning
confidence: 99%